Peramalam Model ARFIMA-GPH dan Intervensi Multi Input pada Indeks Harga Perdagangan Besar Indonesia - Vivi Dina Melani; Miftahuddin; Muhammad Subianto (Hasanuddin University, 2022)
IHPBI is an early indicator in consumer price analysis. When inflation has occurred, Indonesia's economic stability begins to be disturbed, so in order to suppress inflation, the government raises interest rates and when the circulation of money begins to decrease. This study to see IHPBI in the next 3 years through forecasting using the ARFIMA method and multi-input intervention. This is done to find out the movement of the IHPBI over the next 3 years and to compare the two methods. The results obtained show that the selected model is ARFIMA(1,0.1579,0), the January 2009 intervention with ARIMA(1,1,1) of order (b=0, s=1, r=1) and November 2013 intervention with ARIMA(1,1,2) order (b=1, s=1, r=0). The IHPBI forecast for the next 3 years is increasing slowly every month